Proyecto a nivel de ejecución de la carretera Puerto Sangapilla Nuevo Mundo - Escudero Saavedra, Gilber D. (2004)
This thesis work is the applicative type we have made to the opt Professional Civil Engineering degree, in order to carry out a technical and scientific input and contribute to students of undergraduate training and likewise to solve a problem Local roads, which when run will allow for a stretch of highway that will contribute to the socioeconomic development of the beneficiary population. PROJECT LOCATION In a more explanatory way located in the San Martin region in the ubcuenca Valley Biavo the right bank of Huallaga Puerto Sangapilla where begins the stretch. Location: New World District: Under Biavo Province: Bellavista Department: San Martin. The stretch Puerto Sangapilla and New World Km. 0 + 000 to Km. 11 +000 said material has worn the tread uncompacted with a thickness of about 0.1 or 0.15 cm. In the stretches between 9 + 300 and 1 0 + 500 the stretch becomes critical in times of rains which will remove and replace the organic material transported from quarry hill material to improve the subgrade and to place the layer I said. The stretch in the first progressive is hillside constituting this branch in the most critical part of the project which have a strong slope and suffer from landslides that pollute the road surface, therefore the construction of sidewalks arises desquinchado hand as it mentioned in previous paragraphs with their respective drainage to evacuate the water that can accumulate and make their respective reforestation with seedlings Huimba.